Natural rubber/epoxidised natural rubber/polyvinyl chloride ternary blends - Wan Abdul Rahman, Wan Aizan (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1993)

(untitled)
Blends of polyvinyl chloride (PVC) with natural rubber (NR) at all compositions were found to be incompatible and show poor mechanical properties. Nevertheless, PVC with epoxidised natural rubber (ENR) formed miscible blends with good mechanical properties. In recent report, PVC-ENR blends were shown to form cross linked during moulding at elevated temperatures in the absence of any cross linking agent, which ascribe to promising properties. Therefore to achieve enhance mechanical performance of the blends, phases must he compatible to certain extent. A study was conducted to improve the properties of the immiscible NR/PVC system by the insertion of ENR as the ternary component. Preparation of the blends was accomplished on a Brabender Plasticoder PL-2000 utilising a cam-blade mixer with silicone oil heating system. From the mechanical properties analysis, ENR insertion up to 20% showed improvement in the overall mechanical behaviour of the NR/PVC blends at 2:3, 1:1. 3:2 ratio understudied. NR/PVC dissolved readily in tetrahydrofuran (THF), whereas blends of NR/PVC containing ENR up to 20% swells which probably demonstrate the entanglement formation physically or chemically. Different type of ENR influence the blend properties whereby ENR50 is a better compatibilizer or properties modifier for NR/PVC blends. Mixing characteristic also influence properties of the blends. Tensile performance shows that blends Is, the best under optimised conditions. Hardness properties however increases with the increase in speed and temperature for both ENR25 and ENR50. Density of the blends was found to be unchanged, albeit the changes in composition and mixing condition (is 1.05 + 0.01 g/cm3).